AGBL2 promotes cancer cell growth through IRGM-regulated autophagy and enhanced Aurora A activity in hepatocellular carcinoma. (1st February 2018) - Wang, Li-Li; Jin, Xiao-Han; Cai, Mu-Yan; Li, Hai-Gang; Chen, Jie-Wei; Wang, Feng-Wei; Wang, Chen-Yuan; Hu, Wei-Wei; Liu, Fang; Xie, Dan
Abstract: AGBL2 has been reported to catalyze α-tubulin detyrosination, by which it promotes tumorigenesis and cancer progression. However, its potential role in the pathogenesis of hepatocellular carcinoma (HCC) has not been revealed yet. In the present study, AGBL2 was frequently found being overexpressed in HCC tissues and cell lines. In a large cohort of clinical HCC tissues, high expression of AGBL2 was positively associated with tumor size, tumor multiplicity and advanced clinical stage ( p < 0.05), and it was an independent prognostic factor for HCC patients. In HCC cell lines, ectopic overexpression of AGBL2 substantially enhanced HCC cells survival and proliferation in vitro and promoted tumor growth in vivo . In addition, we demonstrated that overexpression of AGBL2 in HCC cells notably inhibited apoptosis by enhancing IRGM-regulated autophagy. Meanwhile, AGBL2 could up-regulate the expression of TPX2 and Aurora A activity to promote cell proliferation in HCC cells. In summary, our findings suggest that up-regulation of AGBL2 plays a critical oncogenic role in the pathogenesis of HCC through modulation on autophagy and Aurora A activity, and it could be a candidate for prognostic marker and therapeutic target in HCC. Highlights: AGBL2 is overexpressed in HCC cells and is an independent prognostic biomarker. AGBL2 promotes HCC cell survival and proliferation. AGBL2 enhances autophagy to protect HCC cell from apoptosis by up-regulating IRGM. AGBL2 up-regulates the expression of TPX2 to enhance Aurora A activation, leading to HCC cell proliferation.